The Relationship between Mothers Characteristic with Anemia in Pregnancy - Pratiwi, Mediya Hesti; Dinengsih, Sri; Novelia, Shinta (Universitas Islam Lamongan, 2023)
Maternal mortality in Indonesia is generally caused by several factors. First, direct obstetrics causes includes bleeding 28%, preeclampsia/eclampsia 24%, infection 11%, while indirect causes include nutritional problems including anemia in pregnant women 40%. Chronic energy deficiency 37%, US well US pregnant women with energy consumption below the minimum requirements of 44.2%. Know the relationship between maternal characteristics and the incidence of anemia in pregnant women at the Gatot Soebroto Army Hospital in 2022. Methods: This research is a quantitative study with a case control design, using primary data with a sample of 102 WUS who visited the Midwifery Polyclinic. the sampling technique uses random sampling. Data analysis using univariate and bivariate using chi square.Research Results: The results of the study showed that 51 respondents (50%) experienced anemia during pregnancy. Variables related to anemia in pregnant women were parity (0.000), ANC visits (0.011), Compliance with consumption of Fe tablets (0.000) and nutritional status (0.000). pregnant women who do not adhere to taking Fe tablets have a risk of 13.6 times experiencing anemia compared to pregnancy to pregnant women who adhere to taking Fe tablets with OR = 13.6. There is a relationship between parity, ANC visits, adherence to consumption of Fe tabletsand nutritional status with anemia in pregnant women. It is expected that pregnant women can prepare for pregnancy well US a way to prevent anemia in pregnancy